Antiseptic Soaking of Tendon Xenografts: A Biomechanical Study on Structural Integrity as a Model for ACL Autografts. - günaydın, fatih; Ceylan, Hasan; Aydin, Mahmud; Muratoğlu, Osman Görkem; Özcecelik, Ada; Yıldırım, Cem; Bozdağ, Ergün (The Journal of Knee Surgery)
Introduction: During anterior cruciate ligament (ACL) reconstruction, intraoperative graft contamination or postoperative infection remains a notable clinical concern. While antiseptic solutions are increasingly employed for graft decontamination and infection prophylaxis, the potential impact of these agents on the biomechanical integrity of tendon grafts has not been fully elucidated. This experimental study aimed to evaluate the biomechanical effects of soaking tendon grafts in vancomycin, chlorhexidine, and povidone-iodine solutions. Methods: Fresh bovine deep digital flexor tendons were used to simulate ACL autografts and randomly assigned to four groups (n = 6): 4% chlorhexidine, 10% povidone-iodine, 5 mg/mL vancomycin, and 0.9% isotonic saline (control). After 30-minute soaking, tendons were sutured using a Four Rip-Stop technique and biomechanically tested using a servohydraulic tensile system. Failure load, stiffness, and cyclic elongation were measured. Statistical analysis was performed using Kruskal-Wallis and Mann-Whitney U tests with Bonferroni correction. Results: Vancomycin and chlorhexidine groups exhibited significantly lower cyclic elongation compared to control and povidone-iodine groups. Failure load was also significantly higher in these groups, particularly compared to povidone-iodine, which demonstrated the weakest biomechanical performance. No significant differences in stiffness were observed across groups. Conclusion: Vancomycin and chlorhexidine can be safely used for short-term antiseptic soaking without compromising graft mechanical integrity. In contrast, povidone-iodine may weaken tendon structure. These findings may guide antiseptic use during ACL reconstruction and in managing contaminated tendons in open injuries.